2019
DOI: 10.48084/etasr.3070
|View full text |Cite
|
Sign up to set email alerts
|

Post Construction and Long Term Settlement of an Embankment Dam Computed with Two Constitutive Models

Abstract: For the settlement computation of an embankment dam, the soil stiffness is of great importance. Unfortunately, due to the lack of funds allocated for geotechnical investigation, stiffness parameters are commonly not evaluated as compared to strength properties. As a result, this may create hindrance in the use of advanced constitutive models such as Hardening Soil Model (HSM). In this study, the settlement with respect to depth and long term settlement of an embankment dam computed with Mohr-Coulomb Model (MCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…We adjusted the fineness of the mesh (global coarseness), as shown in Figure 2. The Mohr-Coulomb model was used on all layers of the dam to calculate displacements and safety factors at the end of construction and during reservoir filling [10,16]. The settlements at the end of the construction of the hydraulic structure may vary significantly from one structure to another [11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adjusted the fineness of the mesh (global coarseness), as shown in Figure 2. The Mohr-Coulomb model was used on all layers of the dam to calculate displacements and safety factors at the end of construction and during reservoir filling [10,16]. The settlements at the end of the construction of the hydraulic structure may vary significantly from one structure to another [11].…”
Section: Methodsmentioning
confidence: 99%
“…It is very well suitable for the modeling of earth dams by considering loading conditions, complex boundaries, irregular geometries, and material characteristics. It enables simulation of their behavior using various behavior laws, resulting in a more realistic imaging [10,11]. Based on these considerations, it can be concluded that the measurements provided by geotechnical and geodesic methods and the results obtained by FEM can only be complementary [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, quick lowering of the reservoir could be necessary in a case of an emergency. The main parameters on which the safety of a dam depends are soil properties, pressure of water, and geometry [1][2][3]. In case of drawdown, pore pressures in the upstream side of the dam reduce which ultimately disturbs the equilibrium conditions of the dam.…”
Section: Imentioning
confidence: 99%
“…In order to ensure the safety of both the existing and the proposed dams in Pakistan, it is necessary to investigate the strength properties of local soils and their effects on the stability of the dams during their service life. There are very few case studies published on the stability issues of dams in Pakistan [3][4][5][6][7][8][9][10][11][12][13]. To the best of our knowledge no parametric analysis on the effects of strength properties on the stability of embankment dams with respect to local site conditions in Pakistan has been published.…”
Section: Imentioning
confidence: 99%
“…Due to the low permeability of soils, excess pore pressure might develop gradually during raising and filling of the reservoir. This increase in excess pore pressure may lead to slope instability or dam failure [13].…”
Section: Imentioning
confidence: 99%